Developement of Adaptive Array for ISDB-T: Filed Experimental Result of Co-Channel Interference Cancellation - Ando, Yoshitaka; Shibuya, Kazuhiko; Takeuchi, Tomoaki; Narikiyo, Yoshikazu; Hamazumi, Hiroyuki (The Journal of The Institute of Image Information and Television Engineers, 2007)
We investigated co-channel interference cancellation in a digital terrestrial broadcast environment. The experiments were performed using a prototype MMSE adaptive array at Telecommunications Advancement Organization of Japan relay stations. We evaluated the cancellation effect for some interference conditions. We also investigated the relationship between the theoretical cancellation effect and the experimental one. The results showed the possibility of the practical use of adaptive array in digital broadcast-wave relay stations.